Pelatihan Jurnalistik bagi Santri Madrasah Diniyah Al-Anwar dalam Mengembangkan Skill Media dan Literasi - Gita Juliwanti; Israyati Rifqoh; Lailatul Mufidah; Nisrinah Firdaus (LPPM Universitas Yudharta Pasuruan, 2020)
The existence of gadget makes many children less creative when it comes to writing and telling stories. In addition, many children access bad news such as violent news, or pornography. Such conditions occur a lot in the jogosari pandaan village area. In this activity, the service team of Yudhartha Pasuruan University strives to provide journalistic training to develop children's creativity in the field of journalists in the form of news writing. In the event there were 25 participants consisting of elementary and junior high students. Facilitators provide knowledge and skills on how to do news writing in accordance with journalistic rules. The participants get a lot of experience related to the way good news writers and true. After the training, participants' interest in the writing of news increases in addition, participants can also clarify various types of news text so that participants are more confident in the writing they have